The Fire Effect on the Performance of Reinforced Concrete Beams with Partial Replacement of Coarse Aggregates by Expanded Clay Aggregates - Abdullah, Alaa H.; Mohammed , Shatha D. (Engineering, Technology & Applied Science Research, 2023)
This paper aims to investigate the flexural behavior of reinforced concrete beams considering fire resistance by adding Lightweight Expanded Clay Aggregates (LECA) to the concrete mix as partial coarse aggregate replacement. LECA is a type of porous clay with a uniform pore structure with fine, closed cells and hard, tightly sintered skin. The experimental work comprised four reinforced self-compacted concrete beams. All the specimens were identical in their geometrical layout of 1600×240×200 mm, reinforcement details, and support condition (simply supported). For all the beams, the main reinforcement was provided by two bars, each having a diameter of 12 mm, while a bar of 6 mm diameter was employed for the top and shear reinforcement. Each beam had a different replacement ratio of LECA for coarse aggregates (0, 10, 20, and 30%). All the specimens were tested under static two concentrated loads after being exposed to the fire of steady-state temperature (500 oC), 1 hr duration, and sudden cooling process. The results showed that adding LECA reduced the number and width of the generated cracks due to fire and reduced the deterioration of the ultimate load capacity and beam rigidity (stiffness).